The role of the gut microbiota in gastric cancer: the immunoregulation and immunotherapy - Wang, Meiqi; Yang, Ge; Tian, Yuan; Zhang, Qihe; Liu, Zhuo; Xin, Ying (Frontiers in Immunology, 2023)
Gastric cancer (GC) is one of the most common cancers, leading to the deaths of millions of people worldwide. Therefore, early detection and effective therapeutic strategies are of great value for decreasing the occurrence of advanced GC. The human microbiota is involved not only in the maintenance of physiological conditions, but also in human diseases such as obesity, diabetes, allergic and atopic diseases, and cancer. Currently, the composition of the bacteria in the host, their functions, and their influence on disease progression and treatment are being discussed. Previous studies on the gut microbiome have mostly focused on Helicobacter pylori (Hp) owing to its significant role in the development of GC. Nevertheless, the enrichment and diversity of other bacteria that can modulate the tumor microenvironment are involved in the progression of GC and the efficacy of immunotherapy. This review provides systematic insight into the components of the gut microbiota and their application in GC, including the specific bacteria of GC, their immunoregulatory effect, and their diagnostic value. Furthermore, we discuss the relationship between the metabolism of microbes and their potential applications, which may serve as a new approach for the diagnosis and treatment of GC.